Does body image dissatisfaction exacerbate smartphone addiction among Chinese college students? - Xu, Peizhe; Shao, Kaichao (Frontiers in Psychology, 2025)
IntroductionIn the context of the widespread use of mobile internet and smartphones, the issue of excessive smartphone uses and even addiction among college students has become an important social concern. However, the relationship between body image satisfaction, which is a key factor influencing psychological state and behavioral choices, and smartphone addiction has not been fully explored.MethodsThis paper focuses on the impact of college students’ body image satisfaction on smartphone addiction. In the theoretical part, this paper constructs a theoretical framework of smartphone addiction based on objectification theory. Using survey data from 1,958 college students in 7 universities across 3 provinces in China, this study evaluates the levels of smartphone addiction and body image satisfaction among Chinese college students using the Smartphone Addiction Scale-Short Version (SAS-SV) and the Body Image State Scale (BISS). In the empirical part, an OLS model is employed to analyze the impact of college students’ body image satisfaction on smartphone addiction.ResultsThe study finds that a 1% decrease in college students’ body image satisfaction leads to a 5.76% increase in smartphone addiction.DiscussionThis conclusion varies by gender and discipline: in terms of gender differences, the impact of body image dissatisfaction on smartphone addiction among female college students is 1% higher than that among male college students; regarding discipline differences, the impact of body image dissatisfaction on smartphone addiction among students in humanities and social sciences is 2% higher than that among students in science and engineering. In the mechanism analysis, it is found that the frequent use of short-video and e-shopping apps among college students further exacerbates the impact of body image dissatisfaction on smartphone addiction.